Tying Knots Between Wound Closure Materials - Yalçın, Can Ege; Demiröz, Anıl; Aydın, Yağmur (Cerrahpaşa Medical Journal, 2022)
Wounds caused either intentionally during procedures or secondarily due to trauma need to be approximated to achieve primary closure. There are many methods to approximate wound edges, with the use of sutures being the most popular and common. Other methods such as staples, tissue adhesives, and strips also exist. This article aims to review the primary tools that are used for wound closure taking their materials into consideration as well. Cite this article as: Yalçın CE, Demiröz A, Aydın Y. Tying knots between wound closure materials. Cerrahpaşa Med J. 2022;46(2):86-90.